2018
DOI: 10.1177/1753193417752891
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the Dutch Unité Rhumatologique des Affections de la Main and its ability to measure change due to Dupuytren’s disease progression compared with the Michigan Hand outcomes Questionnaire

Abstract: Data of a prospective longitudinal cohort study including 233 Dupuytren’s patients was used to determine: (1) whether the Unité Rhumatologique des Affections de la Main scale and Michigan Hand outcomes Questionnaire can detect change in hand function due to Dupuytren’s disease progression and to compare their abilities; (2) the concurrent validity, reliability, responsiveness and interpretability of the Dutch Unité Rhumatologique des Affections de la Main. The Unité Rhumatologique des Affections de la Main and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The two studies with URAM pre-and post-treatment data showed significant clinical response capacity of this scale after treatment [30,32] . In the study by Bernabé et al [16] the favorable psychometric properties of this questionnaire and its ease of use for patients with DD were confirmed [39] .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The two studies with URAM pre-and post-treatment data showed significant clinical response capacity of this scale after treatment [30,32] . In the study by Bernabé et al [16] the favorable psychometric properties of this questionnaire and its ease of use for patients with DD were confirmed [39] .…”
Section: Discussionmentioning
confidence: 82%
“…Pain, which is included in both the DASH and the MHQ, is rarely reported by people with DD, and so can reduce the sensitivity of both tools [35] . While the MHQ may seem adequate for evaluating the DD outcomes, it is long and may not always be duly completed [27,39,40] . The use of the brief MHQ, which saves time in patient evaluations, was the subject of only one study covering 57 DD patient outcomes, although it has shown goodreliability, validity, and high response capacity for patients with DD [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Before injection, patients completed two Dupuytren’s Disease-specific validated patients-reported outcome measures (PROMs): (1) the Unité Rhumatologique des Affections de la Main (URAM) (Broekstra et al., 2018) and (2) Southampton Dupuytren’s Scoring Scheme (SDSS) (Mohan et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…All participants were diagnosed by a physician and inclusion criteria were: Italian mother tongue and no clinically important disease evolution at the present time defined as, no hand surgical intervention in the previous six months and Total Passive Extension Deficit (TPED) changes less than 15 � in each finger between the two data collection points. 16 Exclusion criteria were: age < 18 years old and cognitive deficits. All participants had to give their written informed consent in accordance with the Helsinki Declaration.…”
Section: Participantsmentioning
confidence: 99%
“…10 The estimated clinically important change of the URAM scale in the French population was 2.9 points. 8 The URAM is available in English, French, Danish, Swedish, Hungarian, 10 Dutch, 16 German, 17,18 and Spanish. 19 The purpose of this study was to translate and culturally adapt the URAM into Italian, and investigate the measurement properties (construct validity and reliability) of the URAM-I(10).…”
Section: Introductionmentioning
confidence: 99%